Mining mineral resources from the seabed: Opportunities and challenges. (April 2020) - Watzel, Ralph; Rühlemann, Carsten; Vink, Annemiek
Abstract: The last decade has seen a considerable upsurge in the interest for mineral resources from the deep seabed. In this short comment, the opportunities and challenges of potential future marine extractive activities in the deep sea are highlighted.